Vicarious Liability in Personal Data Protection - Zulian Claudia; Ariawan Gunadi (Rechtsidee: Law Journal, 2023)
This study explores the legal responsibility and ideal concepts in compensating victims of personal data misuse, focusing on the ambiguous regulations within Indonesia's Personal Data Protection Act (UU PDP). The research, conducted through a normative-juridical approach employing conceptual and legislative methods, assessed primary legal materials including UUD NRI 1945 and UU PDP, along with secondary legal materials like books, journals, and non-legal materials such as language dictionaries. The results identified an existing lack of clarity in the UU PDP regarding the embraced accountability concept, potentially impairing the optimal filing of compensation claims by personal data subjects. It concluded that adopting the legal accountability concept of vicarious liability could ensure legal certainty for victims and simplify obtaining compensation for personal data misuse. The study implies the necessity for the adoption of vicarious liability, particularly in compensating victims of data misuse, by future institutions involved in personal data protection.